Molecular Structure, Experimental and Theoretical Vibrational Spectroscopy, and MEP Study of 4-methyl-N-(4-methylphenyl) Benzene Sulfonamide - K.Sarojini; H.Krishnan; Charles C Kanagam; S.Muthu (Science and Technology: Developments and Applications Vol. 5, 2025)
The structural and spectroscopic characterization of the synthesized aromatic organic compound 4-methyl-N-(4-methylphenyl) benzene sulfonamide (abbreviated as 4M4MPBS) was carried out using experimental XRD, FTIR, and FTRAMAN techniques. To support the analytical results, theoretical calculations were performed on 4M4MPBS using the DFT method associated with B3LYP functional with a 6-31G (d,p) basis set. Furthermore, the reactivity of the title compound was studied by the investigation of molecular electrostatic potential (MEP) computed and discussed.